#NoSnowflakes: The toleration of harassment and an emergent gender-related digital divide, in a UK student online culture. (October 2021) - Haslop, Craig; O'Rourke, Fiona; Southern, Rosalynd
In recent years, some political commentators and mainstream media outlets in the United Kingdom have pejoratively labelled young people, especially university students, a 'snowflake generation' – a term used to mock their perceived intolerance and over-sensitivity (Fox, 2016; Gullis, 2017; Slater, 2016; Talbot, 2020). This article challenges this discourse by drawing on findings from a large-scale study ( N = 810) conducted on a university campus in England that critically examined student's perceptions of and attitudes to different forms of online harassment, including abusive, offensive and harassing communications, using survey and interview data. Key findings indicate that online harassment is so pervasive in digitised spaces that it is often viewed as the 'norm' by the student population who appear willing to tolerate it, rather than take actions to address it, which challenges pejorative claims that they are intolerant and easily offended 'snowflakes'. Respondents who identify as female and transgender are more likely to be targeted by online harassment. We argue that the label 'snowflake generation' is diverting attention away from student's everyday experiences of online harassment and its adverse effects, particularly on women and transgendered people, which has the potential to create a gender-related digital divide (Jane, 2018). The implications of these findings for the higher education sector will be outlined.